IJAB DALAM AKAD NIKAH (STUDI KOMPARATIF TENTANG KEABSAHAN REDAKSI IJAB MENURUT FIKIH EMPAT MADZHAB) - Irvan Arisandi; Rahmat Mansur; Muhammad Yusuf Nasir (IAI Al-Mawaddah Warrahmah Kolaka, 2022)
The scholars provide different limits in determining the valid ijab phrases used in the marriage contract, some scholars provide loose limits and some scholars provide strict limits on the valid ijab phrases used in the marriage contract. The marriage contract is an act of worship. So if there are different madhhabs, there will also be different things related to the marriage contract. The focus of the problem is to find how the comparison of the ijab lafadz used in the marriage contract according to the scholars of the four madhhabs and how the comparison of the legal consequences of each ijab lafadz on the validity of the marriage contract according to the Ulama of the four madhhabs. This research uses qualitative research using primary and secondary data, namely books and documents where the object of this research is the opinion of the four madhhabs regarding ijab in the marriage contract with data analysis techniques using descriptive analysis techniques. The results of this study indicate that the Hanafiyah and Malikiyah Madhhabs use lafdh-lafadh whose meaning tends to disrespect the prospective wife. Such as the use of lafadh wahaba which means giving gifts and lafadh mallaka which means giving ownership rights. The Shafi'iyah and Hambali madhhabs can be said to be very humanist madhhabs. This can be seen from the two ijab phrases used in the marriage contract, and only these two phrases are agreed upon as valid. These two phrases are nakaẖa which means to marry and zawwaja which means to marry. These two words only contain the meaning and intention of marriage, and do not contain meanings that tend to disrespect the prospective wife. The Shafi'iyah and Hambali madhhabs impose very strict rules on the validity of the ijab used in the marriage contract. These two madhhabs only legalize the words nakaẖa and zawwaja. They argue that in relation to witnessing the marriage contract, witnessing is an act of witnessing something concrete only and must be clear. So that testimony that is abstract or unclear, let alone still requires a qarinah, the testimony is considered invalid.